Back Massage pada Nyeri Rematik: Sebuah Literature Review - Rubianti, Risma (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2022)
Rheumatism is a disease that attacks the immune system which can cause inflammation of the joints. Due to the pain, rheumatism sufferers are often reluctant to carry out activities, which can interfere with their daily activities. Rheumatism cannot be left alone because rheumatism is a chronic and progressive disease. The aim of this literature review is to determine the effect of back massage therapy on rheumatic pain. This method uses a literature review method obtained based on a literature search carried out by reading various journals, books and other articles related to the subject with a total of 10 journals reviewed. The results of the literature review conclude that back massage is very effective for relieving pain in rheumatism.